The Effect of Classical Music Therapy on The Cognitive Function of The Elderly - Manopo, Monica Jetmin; Memah, Herlina; Warouw, Herman; Keintjem, Femmy; Alow, Getruida Banon Hermina (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2023)
Background: The elderly, better known as the